Alterations of EHD1/EHD4 Protein Levels Interfere with L1/NgCAM Endocytosis in Neurons and Disrupt Axonal Targeting - Yap, Chan Choo C. (Society for Neuroscience, 2010)
Axon growth is regulated by many proteins, including adhesion molecules, which need to be trafficked correctly to axons. The adhesion molecule L1/neuron–glia cell adhesion molecule (NgCAM) travels to axons via an endocytosis-dependent pathway (transcytosis), traversing somatodendritic endosomes. The Eps15 homology domain (EHD) family proteins (EHD1–EHD4) play important roles in endosomal recycling and possibly in endocytosis. We investigated whether EHD1 regulates L1/NgCAM trafficking in neurons. Both short hairpin-mediated downregulation and overexpression of EHD1 led to dendritic mistargeting of NgCAM. Downregulation of EHD1 showed increased endosomal accumulation of NgCAM, whereas, surprisingly, overexpression of EHD1 led to impairment of L1/NgCAM internalization in neurons but not in fibroblasts. Transferrin internalization, however, was unaffected. At longer overexpression times of EHD1, NgCAM endocytosis returned to normal, suggesting rapid upregulation of compensatory endocytic pathways. EHD1 is capable of hetero-oligomerization, and an endogenous complex of EHD1 and EHD4 was identified previously. We therefore tested whether short-term overexpression of other EHD family members showed a similar endocytosis defect. Expression of EHD4, but not of EHD3, also caused a defect in L1/NgCAM endocytosis. Oligomerization of EHD1 was required to cause NgCAM endocytosis defects, and simultaneous expression of EHD1 and EHD4 rescued NgCAM endocytosis. Therefore, balanced levels of EHD1–EHD4 are important for NgCAM endocytosis in neurons. Our data suggest that EHD1 plays roles in both endosomal recycling and a specialized endocytosis pathway in neurons used by NgCAM. We propose that EHD1 and EHD4 act as hetero-oligomeric complexes in this pathway.